Aksesibilitas bagi Anak Berkebutuhan Khusus dalam Lingkup Pendidikan Sekolah Inklusi di Karisidenan Surakarta - Khakim, Abwatie Al; Prakosha, Donni; Himawanto, Dwi Aries (The Center for Disability Studies and Services Brawijaya University, 2017)
This research aims to identify condition of inclusive school in Solo especially for handicapped children. This is a qualitative research. Focuses of this research are first, the accessibility of inclusive school and second, identifying ideal inclusive school for handicapped children. it is located in two schools namely at Al Firdaus High School of Sukoharjo and Brumantakan Elementary School Solo. Method to collect data is observation, interview, and documentation. Conclusion drawn from this research is accessibility of inclusive school for handicapped children is not fulfilled completely. There is still barrier in completing condition of good and proper accessibility in inclusive school.